Strategi Peningkatan Kinerja Pustakawan dalam Menghadapi Perkembangan Teknologi Informasi di Perpustakaan Umum Gunung Bungsu (PUGB) Kabupaten Tanah Datar - Surgana, Feni; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were: (1) to describe the librarians challenges’ at PUGB in dealing with the development of information technology, (2) to describe the strategies that undertaken to increase the performance of librarians in facing the development of information technology at PUGB Tanah Datar. Data were collected by using observation method, interviewing with 7 librarians at PUGB. Analysis was done descriptively. The study objective is the strategy of improvement librarians performances at Public Library of Gunung Bungsu Tanah Datar Regency. There are two findings of the study for librarians in dealing with the developmentthere are two challenges for librarians in dealing with the development of information technology; komputer, communicative and knowledgeable librarians. Based on its challenges, it created the strategy for PUGB librarians in dealing with the the developments of information technology. Keyword: library performance; information technology